Behavioral Finance in Brazil: A Bibliometric Study from 2007 to 2017. Issue 1 (2nd January 2019) - Vitor Jordão da Gama Silva, Paulo; Brandalise Santos, Jordana; Portes Pereira, Gabrielle
Abstract: This article analyzed 58 Brazilian journals in order to address the gap unexplored in the past 10 years by congresses and periodical journals. In this research, an analysis based on keywords was used, followed by analysis of citations and co-citations that allowed to verify: an average growth of 20% p.a. of publications; the most common focus was replication of Kahneman and Tversky; the most studied group tended to be university students; quality has failed to accompany the increase in publications; public institutions publish more. A gap was perceived in the surveying of financial managers and investors, as well as bias and heuristics as a subject.